Design, synthesis, characterization, molecular docking studies, molecular properties, toxicity, and bioactivity score prediction evaluation of novel chalcone-sulfonate hybrid derivatives - Korkmaz, A. (Elsevier B.V., 2023)
Novel chalcone-sulfonate hybrid derivatives were synthesized by a triethylamine-based method and characterized 13C NMR, 1H NMR, and HRMS. The potential inhibitory effects of the synthesized compounds on acetylcholinesterase, butyrylcholinesterase, pancreatic lipase, glutathione s-transferase, tyrosinase, and alpha-amylase enzymes were evaluated by in silico method. The chalcone-sulfonate hybrid derivatives were found to exhibit more effective binding affinity than the glutathione s-transferase, tyrosinase, pancreatic lipase, and alpha-amylase enzyme standards. In addition, six compounds showed more potent affinity values than the acetylcholinesterase standard. Also, seven compounds showed more effective affinity values than the butyrylcholinesterase standard. Furthermore, the absorption distribution, metabolism, and excretion properties (ADME), molecular properties, estimation of toxicity, and bioactivity scores of chalcone-sulfonate hybrid derivatives were evaluated. © 2023 Elsevier B.V.
Keywords: Admet; Bioactivity; Chalcone Compounds; Drug-Likeness; Molecular Docking; Sulfonate Derivatives; Amylases; Binding Energy; Molecular Modeling; Peptides; Toxicity; Acetylcholinesterase; Admet; Chalcone Compound; Chalcones; Drug-Likeness; Molecular Docking; Molecular Properties; Sulfonate Derivatives; Sulphonates; Synthesised; Bioactivity